Specific Inhibitor of Matrix Metalloproteinase Decreases Tumor Invasiveness After Radiofrequency Ablation in Liver Tumor Animal Model - Jiang, An-Na; Liu, Jing-Tao; Zhao, Kun; Wu, Hao; Wang, Song; Yan, Kun; Yang, Wei (Frontiers in Oncology, 2020)
Objective To determine whether the specific inhibitor of matrix metalloproteinase (MMP)—batimastat (BB-94)—could decrease the progression of liver tumor after radiofrequency ablation (RFA) and achieve better therapeutic efficacy in an animal model. Methods In vitro experiments, the proliferation of H22 liver tumor cells was detected by CCK 8 assay and cell migration was detected by Transwell method. In vivo experiments, H22 murine liver tumors were used. First, 32 mice with one tumor were randomized into four groups (n = 8 each group): control (PBS only), RFA alone (65°C, 5 min), BB-94 (30 mg/kg), RFA+BB-94. The growth rate of the residual tumor and the end point survival were calculated and the pathologic changes were evaluated. Secondly, a total of 48 tumors in 24 animals (paired tumors) were randomized into three groups (n = 8 each group): control, RFA alone, RFA+BB-94. Each mouse was implanted with two tumors subcutaneously, one tumor was treated by RFA and the other was evaluated for distant metastasis after applying BB-94. Results In vitro, the proliferation assay demonstrated higher proliferation ability after heat treatment (0.82 ± 0.07 vs 1.27 ± 0.08, P = 0.008), and it could be inhibited by BB-94 (1.27 ± 0.08 vs 0.67 ± 0.06, P = 0.001). In the cell migration assay, the H22 cells demonstrated enhanced tumor invasiveness in the heat group than the control group (33.7 ± 2.1 vs 19.7 ± 4.9, P = 0.011). And it could be significantly suppressed after BB-94 incubation (33.7 ± 2.1 vs 23.0 ± 4.6, P = 0.009). With one tumor animal, the growth rate of the residual tumor in the BB-94+RFA group was slower than that in the RFA alone group (P = 0.003). And combination of BB-94 could significantly prolong the survival of the mice (40.3 ± 1.4d vs 47.1 ± 1.3d, P = 0.002). The expression of CD31 and VEGF at the coagulation margin were decreased after combined with BB-94. With two tumors animal, the growth of metastasis tumor in the BB-94+RFA group was slower than that in the RFA group (P < 0.001). Conclusion BB-94 combined with RFA reduced the invasiveness of the liver tumor and improved the end-point survival. Our data suggested that targeting the MMP process with the specific inhibition could help to increase overall ablation efficacy.